ChemInform Abstract: A Novel Protecting Group Methodology for Syntheses Using Nitroxides. Issue 11 (18th March 2014) - Chalmers, Benjamin A.; Morris, Jason C.; Fairfull‐Smith, Kathryn E.; Grainger, Richard S.; Bottle, Steven E.
Abstract Nitroxides (I) and (IV) are readily protected by a Fenton reaction with DMSO.